Binary and ternary complexes of norfloxacin to improve the solubility of the active pharmaceutical ingredient - Ponce Ponte, Micaela (2018)
Binary and ternary complexes with hydroxypropyl-β-cyclodextrin (HPβCD), using glutamic acid (GA), proline (PRO) or lysine (LIS) as the third component, where developed to increase the solubility and the dissolution rate of norfloxacin (NOR). Methods/results: Complexation was evaluated by phase solubility studies, obtaining the highest NOR solubility with GA and HPβCD. Thermal analysis suggested that different kinds of interactions occur among NOR, HPβCD and each aminoacid (AA) , and when the systems were prepared by kneading or by means of lyophilization. Dissolution studies, performed on simulated gastric fluid and subsequent simulated intestinal fluid, showed the highest rate of NOR from NOR:HPßCD:GA. Conclussion: NOR:HPßCD:GA was the best approach for improving the bioavailability of NOR.KEYWORDS: norfloxacin; hydroxypropyl-β-cyclodextrin; glutamic acid ; proline; lysine; solubility; dissolution rate; Nuclear magnetic resonance; thermal analysis.